Artificial Intelligence Based Chatbot on RasaNLUSystem Empowered with Deep Learning - Maya Bint Yousaf*; Misbah Akram; Ayesha Kamran; Syed Younus Ali; Fariha Ashraf; Muhammad Hassan Nafees; Burhan Ahmed (Spectrum of Engineering Sciences, 2025)
This study explores the development of an interactivecommunication application designed to facilitate the exchangeof information in a user-friendly manner. The applicationallowsindividuals to send queries in simple language andreceiveunderstandable, actionable responses. This feature is particularlybeneficial for users who need specific, detailed informationacrossa variety of topics. The application is designed with accessibilityinmind, enabling users, including students, to easily obtaintheknowledge they require. Additionally, the systemincorporatesabuilt-in guide to help users navigate and utilize the applicationeffectively, ensuring they can operate it independently withoutrequiring external assistance. This guide is instrumental inmakingthe platform user-friendly, fostering self-sufficiency amongindividuals in diverse contexts. Not only does this applicationservepersonal and educational purposes, but it also holds the potential to improve Information Retrieval (IR) relationships. By streamliningthe process of retrieving and delivering information, it ensures thatusers receive relevant data in a timely and efficient manner. The application is also designed to support knowledge disseminationon a global scale, benefiting users in Pakistan as well as inothercountries. Its ability to deliver precise information contributestothe expansion of educational opportunities, particularly inregionswhere access to resources may be limited. In this way, theapplication serves as a valuable tool for bridging knowledgegapsand enhancing the flow of information between different countriesand cultures. Ultimately, this platform fosters educational development and helps users apply newly acquired knowledgetoreal-world situations, promoting both personal growthand broader socio-cultural advancements. The system’s designensuresthat it is accessible and beneficial to a wide range of audiences, improving learning experiences and IR capabilities across borders. Keywords: Artificial Intelligence, Chatbot Development, RASANLUframework, Deep Learning